2006
DOI: 10.1111/j.1468-2982.2006.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Frequent Headache in the General Population: Comorbidity and Quality of Life

Abstract: We studied the nature and extent of comorbidity of chronic frequent headache (CFH) in the general population and the influence of CFH and comorbidity on quality of life. Subjects with CFH (headache on >14 days/month) were identified in a general health survey. We sent a second questionnaire including questions on comorbidity and quality of life to subjects with CFH and subjects with infrequent headache (IH) (1-4 days/month). We recoded comorbidity by using the Cumulative Illness Rating Scale (CIRS) and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 35 publications
1
26
0
1
Order By: Relevance
“…In another family practice study, Weindels et al found that compared to patients with less frequent headache episodes, a group with frequent headaches (≥ 15 days per month) were significantly more likely to have somatic problems, like gastroenterological and musculoskeletal disorders [18], as well as more psychiatric disorders and medication over-use [19]. Both frequent headache and comorbidity were associated with lower quality of life [19].…”
Section: Relationship To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another family practice study, Weindels et al found that compared to patients with less frequent headache episodes, a group with frequent headaches (≥ 15 days per month) were significantly more likely to have somatic problems, like gastroenterological and musculoskeletal disorders [18], as well as more psychiatric disorders and medication over-use [19]. Both frequent headache and comorbidity were associated with lower quality of life [19].…”
Section: Relationship To Other Studiesmentioning
confidence: 99%
“…Both frequent headache and comorbidity were associated with lower quality of life [19]. Compared to hospital specialists, FPs potentially have more information about patients' other conditions and their management as a whole.…”
Section: Relationship To Other Studiesmentioning
confidence: 99%
“…Equally, it has been found that patients with MOH, although characterized by a worsening of headache and reduced quality of life 25,26,27 , seem to have equal patterns of disability compared to patients with episodic migraine without overuse. Although medication overuse seems to have its costs, it also seems to enable patients to retain functioning and achieve valuable goals 28 .…”
Section: Coping With Pain Re-visited: the Pursuit Of Valued Activitiementioning
confidence: 99%
“…Van Suijlekom et al [3] found that migraine, tension-type and cervicogenic headache had similar impacts on individuals' quality of life, although the cervicogenic headache group scored lower on physical function-ing, which the authors related to more headache days in this group. Likewise, Wiendels et al [5] also found that those with chronic frequent headache reported a poorer quality of life than those with infrequent headache. Function and well-being are further diminished in headache patients who have other comorbid pain conditions [6,7] .…”
Section: Introductionmentioning
confidence: 97%
“…While headache could substantially affect well-being [5,21] , its effect on well-being and cognitive factors has not been investigated comprehensively in the elderly population. In addition, chronic headache is often not an isolated pain state but is frequently accompanied by neck pain [22] .…”
Section: Introductionmentioning
confidence: 99%